Three Dimensional Knowledge Management And Explicit Knowledge Reuse - Harsh, O. K. (Journal of Knowledge Management Practice, 2009)
A new model is being proposed for the knowledge management in three dimensions by extending the two dimensional knowledge management models of Nonaka and Takeuchi and MITRE which accounts knowledge reusability as a third dimension. Present work propose that Knowledge reusability play the vital role like knowledge and should be treated independently as a third dimension unlike the model of Nonaka and Takeuchi model where knowledge reusability has not been considered and MITRA’s model in which the knowledge reusability was not considered explicitly. Present research is in continuation to our previous published and presented work on software, data, information and knowledge reusable concepts in the three dimensions. Present work demonstrates analytically that reusable knowledge may enhance the effective knowledge in an organization and should have its independent existence like knowledge assets. Present work may be valuable to manage knowledge in three dimensional knowledge intensive environments where knowledge reusability not only increases the entire knowledge of the organization while it also increases the quality of knowledge.